2018
DOI: 10.1002/ange.201811458
|View full text |Cite
|
Sign up to set email alerts
|

Lichtinduziertes Schalten der Leitfähigkeit von MOFs mit eingelagertem Spiropyran

Abstract: Leitfähige metallorganische Gerüstverbindungen (MOFs) und intelligente,d urchv erschiedene Stimuli anregbare MOFs werden aktuell intensiv aufgrund ihrer Eignung in der Energiegewinnung und -speicherung sowie Signalverarbeitung untersucht. In der vorliegenden Arbeit wurde die elektronische Leitfähigkeit von MOF-Filmen des Typs UiO-67 mit eingelagertem photoschaltbaren nitro-substituierten Spiropyran untersucht. Bei Bestrahlung mit UV-Lichtk ommt es zur reversiblen Isomerisierung des Spiropyrans (SP) von seiner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 46 publications
0
6
0
2
Order By: Relevance
“…UV‐visible absorption studies compare the absorbance of SP and SP‐UiO‐67 wherein the absorption at 550 nm observed upon illumination with UV light attributes to open MC specifies the photoisomerization within MOF film. The DC conductivity measurements at applied potential of 1 V performed for SP and SP‐UiO‐67 revealed enhanced conductivity of 4.1×10 −9 Sm −1 for SP‐UiO‐67 films aid to design photoelectronic devices with better conductivity in future (Figure ) . Another report from Zhang et al ., analysed the photochromism in cadmium based metal‐organic frameworks comprising of N, N′ ‐di(4‐pyridylacylamino)‐1,4,5,8‐naphthalenediimide (IsoNDI) as ligand with aromatic dicarboxylic acids‐2, 6‐naphthalenedicarboxylic acid (2,6‐H 2 NDC), isophthalic acid (m‐H 2 BDC) and terephthalic acid (p‐H 2 BDC) which act as secondary linkers.…”
Section: Utilization Of External Stimuli Sourcesmentioning
confidence: 82%
“…UV‐visible absorption studies compare the absorbance of SP and SP‐UiO‐67 wherein the absorption at 550 nm observed upon illumination with UV light attributes to open MC specifies the photoisomerization within MOF film. The DC conductivity measurements at applied potential of 1 V performed for SP and SP‐UiO‐67 revealed enhanced conductivity of 4.1×10 −9 Sm −1 for SP‐UiO‐67 films aid to design photoelectronic devices with better conductivity in future (Figure ) . Another report from Zhang et al ., analysed the photochromism in cadmium based metal‐organic frameworks comprising of N, N′ ‐di(4‐pyridylacylamino)‐1,4,5,8‐naphthalenediimide (IsoNDI) as ligand with aromatic dicarboxylic acids‐2, 6‐naphthalenedicarboxylic acid (2,6‐H 2 NDC), isophthalic acid (m‐H 2 BDC) and terephthalic acid (p‐H 2 BDC) which act as secondary linkers.…”
Section: Utilization Of External Stimuli Sourcesmentioning
confidence: 82%
“…Recently,H einkesg roup conducted an in-depth study into conductance modulation in aU iO-67 scaffold with embedded spiropyran photoswitches. [63] Although previous studies had shown regulation of conductivity upon isomerization in single molecules and self-assembled monolayers of spiropyrans,u tilization of these concepts in at hree-dimensional material is novel and could offer untapped potential. In addition to documenting a1 0-fold spike in current upon irradiation with UV light, they also noted the relatively slower isomerization back to the closed form.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Correspondingly,t he isomerization of the previously introduced spiropyrans (SP,see Section 2.1) into merocyanine (MC) can not only be induced by mechanical forces,but also by,f or example,t emperature,p H, solvation, or light. [193][194][195][196][197][198][199][200] Intriguingly,S P-based self-reporting systems have been developed that respond to several stimuli simultaneously. [46][47][201][202][203][204] Forexample,Qui et al reported the synthesis of poly(hydroxyethyl acrylate) with incorporated SPs,w hich changed color upon light irradiation or swelling in water.…”
Section: Angewandte Chemiementioning
confidence: 99%